The Role of Cerclage in Subsequent Pregnancy following Previable Prelabor Rupture of Membranes - Bart, Yossi; Fishel Bartal, Michal; Plaschkes, Roni; Sebag, Diklah; Chauhan, Suneet P.; Sibai, Baha M.; Meyer, Raanan; Kassif, Eran; Yoeli, Rakefet; Mazaki-Tovi, Shali (American Journal of Perinatology, 2023)
Objective This study aimed to ascertain the outcomes associated with a cervical cerclage among individuals with a history of previable prelabor rupture of membranes (PROM).Study Design This study was a retrospective cohort study conducted at a single tertiary center between 2011 and 2021. We included individuals with a history of previable (before 24 weeks) PROM and the subsequent viable pregnancy. Women with multifetal gestation, preterm birth (PTB) or cerclage in previous gestation, or abdominal cerclage after trachelectomy were excluded. Primary outcome was PTB rate (delivery <37 weeks). Recurrence of preterm PROM and adverse composite maternal and neonatal outcomes (CMO and CNO) were evaluated as secondary outcomes. CMO included any of the following: suspected chorioamnionitis, endometritis, red blood cell transfusion, uterine rupture, unplanned hysterectomy, or death. CNO included any of the following: previable PTB (<24 weeks of gestation), bronchopulmonary dysplasia, grade 3 or 4 intraventricular hemorrhage, necrotizing enterocolitis, mechanical ventilation, seizures, hypoxic ischemic encephalopathy, or death.Results During the study period, 118 individuals had a history of previable PROM and a documented subsequent pregnancy, out of which 74 (62.7%) met inclusion criteria. Nineteen (25.7%) of eligible individuals underwent a cerclage for prior previable PROM and were compared with controls (n = 55, 74.3%). Women who underwent a cerclage had higher rates of PTB < 37 weeks (63.2 vs. 10.9%, p < 0.001; odds ratio [OR]: 14.00, 95% confidence interval [CI]: 3.97–49.35) and < 34 weeks (21.1 vs. 3.6%, p = 0.03; OR: 7.07, 95% CI: 1.18–42.39) compared with those without cerclage. Furthermore, recurrent preterm PROM and previable PTB rates were higher among patients who underwent cerclage. The survival curve further indicated that individuals with cerclage delivered earlier. CMO and CNO rates were similar in those with and without cerclage.Conclusion Cerclage placement in individuals with prior previable PROM was associated with higher rates of recurrent preterm PROM and PTB.Key Points
Keywords: prelabor rupture of membranes; previable; preterm birth; cerclage